The public management of risk: separating ex ante and ex post monitors - Yolande Hiriart; David Martimort; Jerome Pouyet (Fondazione Eni Enrico Mattei (FEEM), 2010)
When a firm undertakes risky activities, the conflict between social and private incentives to implement safety care requires public intervention which can take the form of both monetary incentives but also ex ante or ex post monitoring, i.e., before or after an accident occurs. We delineate the optimal scope of monitoring depending on whether public monitors are benevolent or corruptible. We show that separating the ex ante and the ex post monitors increases the likelihood of ex post investigation, helps prevent capture and improves welfare.
Keywords: L51; D82; 330; Risk Regulation; Monitoring; Capture; Integration; Separation